An Evaluation of the Design and Usability of a Novel Robotic Bilateral Arm Rehabilitation Device for Patients with Stroke - Pei, Yu-Cheng; Chen, Jean-Lon; Wong, Alice M. K.; Tseng, Kevin C. (Frontiers in Neurorobotics, 2017)
Study design: case series. Introduction: Robot-assisted therapy for upper limb rehabilitation is an emerging research topic and its design process must integrate engineering, neurological pathophysiology and clinical needs. Purpose of the Study: This study developed/evaluated the usefulness of a novel rehabilitation device, the MirrorPath, designed for the upper limb rehabilitation of patients with hemiplegic stroke. Methods: The process follows Tseng’s methodology for innovative product design and development, namely two stages, device development and usability assessment. During the development process, the design was guided by patients’ rehabilitation needs as defined by patients and their therapists. The design applied synchronic movement of the bilateral upper limbs, an approach that is compatible with the bilateral movement therapy and proprioceptive neuromuscular facilitation theories. MirrorPath consists of a robotic device that guides upper limb movement linked to a control module containing software controlling the robotic movement. Results: Five healthy subjects were recruited in the pre-test, and 4 patients, 4 caregivers and 4 therapists were recruited in the formal test for usability. All recruited subjects were allocated to the test group, completed the evaluation and their data were all analyzed. The total system usability scale (SUS) score obtained from the patients, caregivers and therapists was 71.8±11.9, indicating a high level of usability and product acceptance. Discussion and Conclusions: Following a standard development process, we could yield a design that meets clinical needs. This low-cost device provides a feasible platform for carrying out robot-assisted bilateral movement therapy of patients with hemiplegic stroke. (clinical trial registration number NCT02698605)